2015
DOI: 10.1016/j.jssc.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Structure, stability, and photoluminescence in the anti-perovskites Na3W1−Mo O4F (0≤x≤1)

Abstract: a b s t r a c tSingle-phase ordered oxyfluorides Na 3 WO 4 F, Na 3 MoO 4 F and their mixed members Na 3 W 1 À x Mo x O 4 F can be prepared via facile solid state reaction of Na 2 MO 4 Á 2H 2 O (M¼ W, Mo) and NaF. Phases produced from incongruent melts are metastable, but lower temperatures allow for a facile one-step synthesis. In polycrystalline samples of Na 3 W 1 À x Mo x O 4 F, the presence of Mo stabilizes the structure against decomposition to spinel phases. Photoluminescence studies show that upon excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…After careful analysis of the first principles calculation results and other sufficient investigation, the efficient emission of the Na 2 WO 2 F 4 phosphor originates from the strong parity-allowed absorption of the O-2p to W-5d charge transfer band. Sullivan 103 synthesized the ordered oxyfluorides Na 3 W 1− x Mo x O 4 F (0 ≤ x ≤ 1). The Na 3 WO 4 F structure can be described as a hexagonal anti-perovskite, where the WO 4 tetrahedra occupy the 12-coordinate A site and F − is located on the B site and is octahedrally coordinated by the Na cations, as shown in Fig.…”
Section: Types and Configurational Relationshipmentioning
confidence: 99%
“…After careful analysis of the first principles calculation results and other sufficient investigation, the efficient emission of the Na 2 WO 2 F 4 phosphor originates from the strong parity-allowed absorption of the O-2p to W-5d charge transfer band. Sullivan 103 synthesized the ordered oxyfluorides Na 3 W 1− x Mo x O 4 F (0 ≤ x ≤ 1). The Na 3 WO 4 F structure can be described as a hexagonal anti-perovskite, where the WO 4 tetrahedra occupy the 12-coordinate A site and F − is located on the B site and is octahedrally coordinated by the Na cations, as shown in Fig.…”
Section: Types and Configurational Relationshipmentioning
confidence: 99%
“…51 X-ray intensity data sets for 3, 5, and 6 were collected at 100(2) K using a Bruker D8 QUEST diffractometer equipped with a PHOTON 100 CMOS area detector and an Incoatec microfocus source (Mo Ka radiation, λ = 0.71073 Å). 41 The detector was operated in the shutterless mode with an additional low-angle "fast scan" to account for overtopped pixels. Data collections covered the full sphere of reciprocal space to 2θ max = 72.8°(d = 0.60 Å), with an average reflection redundancy of at least 8.0.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The structural anti designation is of particular importance to this work. The anti designation of the perovskite, , or any other structure for that matter, is given when the positions of the cations and anions are reversed in the structure. Thus, in an anti- perovskite ABX 3 structure, the A and B sites that normally hold the cations are occupied by anions, while the X site that normally holds the anion is occupied by cations.…”
Section: Introductionmentioning
confidence: 99%
“…This group has previously shown that Na 3 Mo 1-x W x O 4 F (0 ≤ x ≤ 1) (Figure 1) is a new family of self-activating oxyfluoride phosphors with 2H anti-perovskite related structure. 21 These materials are isostructural with the known sodium tungsten oxyfluoride Na 3 WO 4 F, 22,23 as determined by Rietveld analysis based upon neutron powder diffraction data of the molybdenum-containing analogues Na 3 MoO 4 F and Na 3 Mo 0.5 W 0.5 O 4 F. Photoluminescence studies show that upon excitation with λ = 254 nm and λ = 365 nm, Na 3 Mo 1-x W x O 4 F (0 ≤ x ≤ 1) materials exhibit broad self-activated emission maxima centered around 485 nm and these materials are also amenable to doping with emitters such as Eu 3+ . 21 Following on from this research, because Na 3 Mo 1-x W x O 4 F (0 ≤ x ≤ 1) has been shown to be amenable to aliovalent doping with trivalent rare earth cations, incorporation of dopant amounts of Ce 3+ into Na 3 MoO 4 F according to Na 3-3a Ce a MoO 4 F (0 ≤ a ≤ 0.25) has been investigated.…”
mentioning
confidence: 99%
“…Na 2 WO 4 and NaF. 21 The spinel structure of Na 2 WO 4 is a cubic close packed array of oxygen with Na atoms filling half of the octahedral holes and W atoms occupying an eighth of the tetrahedral holes. Alternatively, in terms of polyhedra, this structure can be viewed as chains of edgesharing NaO 6 octahedra interspersed with isolated WO 4 tetrahedra (Figure 2).…”
mentioning
confidence: 99%